Health-related Services in Multilateral and Preferential Trade Arrangements in Asia and the Pacific - Mia Mikic (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
In many developing countries, the health-care sector is under-developed, lacking basic infrastructure and human capital, and attracting little attention from investors and policymakers. While encouraging globalization and trade may aggravate those problems and create additional costs in some circumstances, trade liberalization and deeper integration into the global economy could also provide opportunities and resources to address those problems more effectively. This paper contributes to the debate by reporting on the status of liberalization achieved in the health services sector by members of ESCAP through their regional and multilateral trade liberalization commitments.
Keywords: F13; F15; I19; 330; Health services trade; GATS; TRIPS; Preferential Trade Aggreeemetns; Modes of Services Delivery; ASEAN